The Role of Information Technology Media Optimization for the Implementation of Education - Titin; Djone Georges Nicolas; Kariani Zebua; Akito Isiez; Alexander J Hakim (PT FORMOSA CENDEKIA GLOBAL, 2023)
Information technology, which should be utilized to develop and maximize the delivery of education, is sometimes not utilized optimally. At SMP N 1 Ledo, the achievement to be obtained through this research is the effectiveness of IT media for the implementation of Christian Religious Education. The case study method is combined with a qualitative approach in this study. The results of this study indicate that teachers need proper training and support to incorporate technology into classroom learning and IT media has the potential to increase the efficiency of Christian Religious Education learning.